The role of community benefit agreements in natural resource governance and community development: Issues and prospects. (October 2021) - Gunton, Cameron; Markey, Sean
Highlights: Community benefit agreements have become common resource governance instruments. Systematic review reveals conflicting views on role of community benefit agreements. Interplay between conflicting views of agreements leads to better agreements. Research priority is to evaluate agreements and develop best practice guidelines.